Efficacy of Fungicide Against Mould (Fusarium Solani Sacc.) and Stain (Lasiodiplodia Theobromae Pat.) Fungi on Four Clones of Heveawood - Osman, Noridah (2001)
New formulations of safe preservatives are being searched to treat heveawood to resolve discolouration problem so as to preserve and protect its original colour. Sodium pentachlorophenate (NaPCP) has been widely used to control stain fungi on heveawood. However, this substance has been phased out due to its mamalian hazardous. This study was conducted to determine the efficacy of Evotek® 230 SE against wood staining fungi on four clones of heveawood. A formulation of Evotek® 230 SE was tested at various concentrations to control wood staining fungi in four clones of heveawood. The solution concentrations used in this study were 0.1, 0.25 and 0.5%. A concentration level of 0.5 and 1% for sodium pentachlorophenate was used as a standard. Laboratory studies using freshly cut heveawood blocks, demonstrated the antifungal properties of Evotek® 230 SE. This formulation was effective for protection against stain fungi at a low level (0.1%) while sodium pentachlorophenate was effective only at 1.0%.